Guiding exploration through three-dimensional virtual environments : A cognitive load reduction approach. - Chen, Chwen Jen; Wan, Mohd Fauzy (Association for the Advancement of Computing in Education (AACE), 2008)
The real-time interactive nature of three-dimensional virtual environments (VEs) makes this technology very appropriate for exploratory learning purposes. However, many studies have shown that the exploration process may cause cognitive overload that affects the learning of domain knowledge. This article reports a quasi-experimental study that investigates the effects of guiding the exploration through three-dimensional VEs on learning. The results of this study show that the inclusion of additional navigational aids (tracer and directional arrows) to guide the exploration through VEs provides significant learning effects when compared with the use of VEs that do not provide such aids. These results are discussed with respect to theories related to cognitive load.